A temperate river estuary is a sink for methanotrophs adapted to extremes of pH, temperature and salinity. Issue 1 (22nd January 2016) - Sherry, Angela; Osborne, Kate A.; Sidgwick, Frances R.; Gray, Neil D.; Talbot, Helen M.
Summary: River Tyne (UK) estuarine sediments harbour a genetically and functionally diverse community of methane‐oxidizing bacteria (methanotrophs), the composition and activity of which were directly influenced by imposed environmental conditions (pH, salinity, temperature) that extended far beyond those found in situ . In aerobic sediment slurries methane oxidation rates were monitored together with the diversity of a functional gene marker for methanotrophs ( pmoA ). Under near in situ conditions (4–30°C, pH 6–8, 1–15 g l −1 NaCl), communities were enriched by sequences affiliated with M ethylobacter and M ethylomonas spp. and specifically a M ethylobacter psychrophilus ‐related species at 4–21°C. More extreme conditions, namely high temperatures ≥ 40°C, high ≥ 9 and low ≤ 5 pH, and high salinities ≥ 35 g l −1 selected for putative thermophiles ( M ethylocaldum ), acidophiles ( M ethylosoma ) and haloalkaliphiles ( M ethylomicrobium ). The presence of these extreme methanotrophs (unlikely to be part of the active community in situ ) indicates passive dispersal from surrounding environments into the estuary.